RECONSTRUCTING THE MEANING OF SUCCESS AMONG YOUNG PEOPLE AMID ECONOMIC UNCERTAINTY: A DA’WAH COMMUNICATION MANAGEMENT FRAMEWORK - Cut Syamsidar; Ahmad Tamrin Sikumbang; Erwan Efendi (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
Economic uncertainty driven by digital transformation, technological disruption, labor market volatility, and global economic instability has reshaped young people's perceptions of success. Rather than being defined solely by material achievement, success is increasingly understood as a multidimensional concept encompassing psychological well-being, work-life balance, social contribution, economic resilience, and spiritual fulfillment. This transformation presents new challenges and opportunities for da'wah communication in guiding value formation among young people. Therefore, this study aims to analyze the role of Da'wah Communication Management in reconstructing young people's meaning of success amid economic uncertainty and to develop a conceptual framework that integrates communication management with Islamic values. This study employed a Scoping Literature Review approach following the PRISMA-ScR framework. Seven relevant articles published between 2020 and 2025 were identified through a systematic search and analyzed using thematic synthesis to examine patterns, concepts, and relationships among economic uncertainty, the construction of success, and da'wah communication. The findings indicate that economic uncertainty has shifted young people's orientation of success from predominantly material goals toward a more holistic perspective influenced by social interaction, digital communication, and Islamic values. Furthermore, the review demonstrates that effective reconstruction of the meaning of success requires strategically managed da'wah communication through the integrated functions of planning, organizing, implementing, and evaluating communication activities. The novelty of this study lies in the development of a conceptual model of Da'wah Communication Management that integrates communication management theory, social construction theory, and Islamic values into a unified framework for reconstructing young people's meaning of success. This model contributes theoretically to the advancement of Islamic communication studies and offers practical guidance for da'wah institutions, educational organizations, and policymakers in developing communication strategies that foster holistic, ethical, and resilient perspectives on success among young people.